Azathioprine therapy for steroid-resistant Henoch-Schönlein purpura: a report of 6 cases. Issue 1 (December 2016) - Fotis, Lampros; Tuttle, Paul; Baszis, Kevin; Pepmueller, Peri; Moore, Terry; White, Andrew
Abstract Background A small percentage of children with Henoch-Schönlein purpura (HSP) develop a chronic form of the disease that often requires prolonged corticosteroid therapy. Disease modifying anti-rheumatic agents (DMARDs) or biologics have been successfully used to treat those refractory cases. Azathioprine is a DMARD that has been reported to be effective in HSP nephritis and in adult cutaneous leukocytoclastic vasculitis, a condition with cutaneous histology similar to HSP. Case presentation A description of 6 cases with relapsing HSP without significant renal involvement, treated with azathioprine are reported. All 6 cases met the classification criteria for the diagnosis of HSP, had relapsing symptoms despite corticosteroid use, were successfully treated with azathioprine and were tapered off of corticosteroids. The duration of azathioprine therapy ranged from 7–21 months and no adverse events were reported. Conclusions Azathioprine is effective in controlling prolonged relapsing symptoms of HSP, allowing earlier discontinuation of corticosteroids. This report shows that azathioprine can be included in the therapeutic options for relapsing HSP and is the first case series in the literature of azathioprine use in HSP without significant renal involvement.